The montreal cognitive assessment as a screening tool for preoperative cognitive impairment in geriatric patients - Phongthara Vichitvejpaisal (2018)
© 2015, Medical Association of Thailand. All rights reserved. Objective: Study the prevalence of cognitive impairment using the Montreal Cognitive Assessment (MoCA), its relationship to physiologic age-related change, and the preoperative drugs used in geriatric patients. Material and Method: At the preoperative visit, the co-researchers invited 322 general/vascular patients (190 male, 132 female) and 260 urological patients (220 male, 40 female) who met the inclusion criteria and were scheduled for elective surgery to join the study. They went for the MoCA interview, and their preoperative drugs used were recorded in a medication reconciliation file. A cut-off score 24 or above was considered normal. Results: Ninety-two general/vascular and 126 urological patients had taken drugs before admission, but those did not show any correlation with the MoCA score. There were 231 and 91 general/vascular patients and 175 and 85 urological patients with formal education of less than six years and equal/more than six years respectively. The 286 and 36 general/vascular patients and 212 and 48 urological patients posted scores of less than 24 and equal/more than 24 respectively. Gender and education correlated positively and significantly with the score; however, age proved negatively significant. Conclusion: The prevalence of cognitive impairment featured highly in preoperative geriatric patients. The gender, age, and education but not preoperative drugs used affected cognitive function.